STRATEGI MODEL TEAM GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN MINAT BELAJAR MATEMATIKA PADA SISWA SDN SOROPADAN SURAKARTA - Prastiwi, Zanuar; Muhroji, Muhroji; Rani Hapsari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Team Games Tournament (TGT) model is a game-based learning approach that emphasizes teamwork and healthy competition to enhance student engagement in the learning process. In this context, TGT was implemented to improve mathematics learning interest among students at SDN Soropadan Surakarta. Two groups of students were tested: an experimental group using the TGT model and a control group following conventional teaching methods. Pre-test s and post-test s were employed to measure changes in mathematics learning interest. Analysis results indicate that the application of the TGT model led to a significant increase in students' interest in learning mathematics compared to the conventional method. The average score improvement in the experimental group suggests that TGT is effective in creating a more engaging and motivating learning environment. The greater variability in scores within the experimental group highlights a broad positive impact, despite individual differences. In conclusion, the TGT model proves to be an effective strategy for enhancing mathematics learning interest and holds significant potential for broader application in primary education.